Studi Dokumenter Hasil Belajar Psikomotorik Siswa SMA pada Materi Sistem Pernapasan Melalui Model Pembelajaran Project Based Learning (PjBL) - Reny Dwi Riastuti; Yuli Febrianti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the effectiveness of the Project Based Learning model on the respiratory system material in class XII 3 of SMAN 5 Lubuklinggau. The method used in this research is qualitative through a triangulation approach. The results showed that the psychomotor learning outcomes of class XII 3 students on the respiratory system material used the Project Based Learning effective model. In conclusion, the application of the Project Based Learning model is effectively used on respiratory system materials in class XII 3 in virtual learning during the pandemic. Keywords: Effectiveness, Project Based Learning, Psychomotor